2004
DOI: 10.1103/physrevlett.93.235502
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition and Intermixing of Amorphous Water and Methanol

Abstract: The diffusion of molecules in amorphous water and methanol films has been investigated on the basis of time-of-flight secondary ion mass spectrometry as a function of temperature. The glass-liquid transition of the amorphous water film occurs at 130-145 K as confirmed from the surface segregation of embedded methanol molecules. The morphology of the pure amorphous water film changes drastically at 160 K as a consequence of dewetting induced by the surface tension and the strongly decreased viscosity of the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
141
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(152 citation statements)
references
References 15 publications
10
141
1
Order By: Relevance
“…The TPD peak observed at 112 K in Fig. 2 can therefore be attributed to the desorption of OCS from the methanol ice as it undergoes a phase transition (Souda 2004), analogous to the trapping and release observed for OCS binary water ices.…”
Section: Resultsmentioning
confidence: 73%
“…The TPD peak observed at 112 K in Fig. 2 can therefore be attributed to the desorption of OCS from the methanol ice as it undergoes a phase transition (Souda 2004), analogous to the trapping and release observed for OCS binary water ices.…”
Section: Resultsmentioning
confidence: 73%
“…A large decrease in scattered ion intensity was observed in the 130-155 K window due to the desorption of CH 3 OH molecules. The desorption of methanol was visible as pressure increase in the vacuum gauge, starting at ∼130 K. Because of this, crystallization of methanol, supposed to occur at 120 K, 32 was indistinguishable. Moreover, we doubt whether the crystallization in methanol could be observable as a change in ion intensity since the crystallization of water ice was not reflected in ion intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrational spectroscopy, 15 electron diffraction, 10 X-ray absorption spectroscopy, 16 electron spectroscopy, 17 TPD, 18 Kelvin probe, 13 and secondary ion mass spectrometry (SIMS) 19 are some of the experimental techniques used to understand the physics and chemistry of ice. Several of these techniques have been employed to investigate surface structure and morphological changes of amorphous ice.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the T g of vapor-deposited methanol films begins at 80 K, which is 23 K lower than its calorimetric T g (22). In addition to water and alcohol, n-alkanes with no apparent T g have also been studied.…”
Section: The Phase Transitionmentioning
confidence: 99%
“…Desorption of molecules from ice surfaces can be accompanied by processes in the surface that include diffusion (18)(19)(20)(21), molecular volcano (19), crystallization (22,23), and polymerization events, all of which have been the subjects of detailed studies. We can better understand the molecular details of processes taking place in such solids by using vibrational spectroscopy, which in conjunction with TPD is often an indispensable tool .…”
Section: Introductionmentioning
confidence: 99%